2009
DOI: 10.4038/sljch.v30i3.847
|View full text |Cite
|
Sign up to set email alerts
|

A relational analysis of acute wheezing and air pollution

Abstract: Objective To correlate hospital attendance for wheezing treated with nebulizer therapy with pollutant levels recorded in ambient air in Colombo.Setting Emergency treatment unit (ETU) of the Lady Ridgeway Hospital, Colombo.Design A prospective observational case control study.Method Attendance at the ETU for nebulizer therapy was recorded daily for 12 months. ETU attendance for conditions other than wheezing served as controls. The case and control attendance rates were correlated with daily maximum and minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Pollution is often not confined to one pollutant, and synergic effects of pollutants could be more damaging to health than one. Our own studies on health effects established a link between air pollution and wheezing in children in Colombo [2]. In 1998 we observed a concomitant increase in oxides of nitrogen and SO 2 and increased incidence of acute wheezy episodes in December to January.…”
mentioning
confidence: 65%
“…Pollution is often not confined to one pollutant, and synergic effects of pollutants could be more damaging to health than one. Our own studies on health effects established a link between air pollution and wheezing in children in Colombo [2]. In 1998 we observed a concomitant increase in oxides of nitrogen and SO 2 and increased incidence of acute wheezy episodes in December to January.…”
mentioning
confidence: 65%
“…(Karunasekara et al, 2001(Karunasekara et al, , 2005Lankathilaka et al, 2000;Premaratna et al, 2002). Senanayake et al (2001) include the effectiveness of analysing the particulate matter (PM 10 , PM 2?5 ) and elemental analysis (Senevirathne, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Among the transport-induced pollutants that taint urban air, fine particulate matter (PM), sulfur dioxide and nitrogen oxides pose the most widespread and acute health risks in Colombo, Sri Lanka (Senanayake et al, 2001). Unfortunately, urban planning regulations in Sri Lanka have historically contributed to misallocation of land use and led to the growth of an urban form not necessarily conducive to economic development or air quality improvement.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the daily counts of patients nebulized at the OPD of THK was the most practical indicator of daily exacerbation of acute wheezing in the population catered by THK for a retrospective study. This indicator had been used in the past in similar studies done in Colombo, Sri Lanka and in other countries [10,16,17]. Therefore, our specific objective was to study the correlation between daily counts of patients nebulized at the OPD of THK and daily local meteorological parameters.…”
Section: Objectivesmentioning
confidence: 99%
“…Despite the above background, only a few studies were done in Sri Lanka and in other parts of South Asia on the correlation between wheezing and atmospheric conditions [9,10]. Those Sri Lankan studies were also concerned only with air pollution (meteorological parameters were not considered).…”
mentioning
confidence: 99%